Urban governance and the environment: an Irish case study - Fagan, Honor G.; Murray, Michael (Centre for Urban and Regional Studies. Trinity College Dublin, & the Faculty of the Built Environment, Dublin Institute of Technology. Bolton Street, 2004)
This article explores the general comparative issues arising in relation to urban environmental governance through a particular Irish case study. The particular issue was/is the siting of a waste incinerator in a working class suburb of Dublin and the popular campaign of resistance against it that emerged. Since then the Irish government has simply abolished the local level of government in relation to urban waste management and the politics of waste has become a sharply divisive issue. What we will do here is outline first the main parameters of the 'waste crisis' in Ireland and then examine how its governance was approached in the late 1990's. We then turn to a case study of a particular local urban campaign against incineration and is subsequent generalisation as waste became the main battle-ground in the contested terrain of urban governance in Ireland. Finally, some general implications of this study are drawn out.
Keywords: Urban geography -- Ireland